Proses Pembentukan Kata dalam Kumpulan Cerpen 1 Perempuan 14 Laki-Laki Karya Djenar Maesa Ayu - Risa Octarini, Eighty; Darma Laksana, I Ketut; Widarsini, Ni Putu N (Humanis, 2017)
This research aims to analyze the process of word formation in the short story collection 1 Perempuan 14 Laki-Laki by DjenarMaesa Ayu. The data used in this research was obtained from the book that contains 14 short stories in it. Collecting data in this research using simak method . Data were analyzed by applying the agih method , by exposing using the morphology theory. With the approach and the theory, presented the process of word formation in the short story collection 1 Perempuan 14 Laki-Laki by Djenar M aesaAyu. The process of word formation in the short story collection 1 Perempuan 14 Laki-Laki by DjenarMaesa Ay u consists of affixation, reduplication, and composition. The process of word formation examined on the form, function , and meaning. Affixation consist of a prefix, infix, suffix, convix , and simulfix. Prefixes that found in the collection of short stories 1 Perempuan 14 Laki-Laki by DjenarMaesa Ay u are meng-, ke -, ber-, di-, se- , per-, p eng - , and ter- . Infix es that found are -el- and -em-. Suffixes that f ound are -an, -i, -kan, and -nya . Confixes that found are ke- ... -an, ber- ... -an, per- ... -an, p eng - ... -an, and se- ... -nya . Meanwhile, simulfix es that found are meng- ... -kan, meng- ... -i, and meng- per ... -kan. Besides affixation , there is a process of word forming by reduplication. The r eduplication s that found are morphological reduplication. Morphological reduplication consists of two kinds, namely root reduplication and affixed reduplication . Beside that, there are also the process of word formation through the composition. The composition that found only nominal composition. Nominal composition consists of g rammatical meaningful nominal composition and idiomatic meaningful nominal composition.